Flying over Brazilian Organizations with Zeppelin: A Preliminary Panoramic Picture of Continuous Software Engineering - Santos Júnior, Paulo Sérgio; Barcellos, Monalessa Perini; Ruy, Fabiano Borges; Omêna, Moises Savedra (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Context: Software organizations have faced several challenges, such as the need for faster deliveries, frequent changes in requirements, lower tolerance to failures and the need to adapt to contemporary business models. Agile practices have allowed organizations to shorten development cycles and increase customer collaboration. However, this has not been enough. Organizations should evolve to continuous and data-driven development in a continuous software engineering approach. Continuous Software Engineering (CSE) consists of a set of practices and tools that support a holistic view of software development with the purpose of making it faster, iterative, integrated, continuous and aligned with business. Implementing CSE requires changes in the organization’s culture, practices and structure, which may not be easy. Objective: We aim to provide a preliminary picture of CSE adoption in Brazilian organizations. Method: We adapted and used Zeppelin, a diagnostic instrument of CSE adoption based on the Stairway to Heaven Model (StH) to perform a survey with 28 Brazilian organizations aiming at investigating the adoption of CSE practices. Results: The results indicate that organizations have better addressed agile and continuous deployment practices than the ones related to continuous integration and continuous experimentation, but this scenario changes a bit depending on the organization type. They also show that CSE adoption has been heterogeneous, but there are patterns in the adoption of some practices. Conclusion: Although the StH model proposes a sequential and evolutionary path for CSE adoption, organizations have not always followed it systematically. There are indeed CSE practices that depend on others and thus contribute to sequential implementation. However, organizations tend to adopt the practices gradually, covering different stages, and evolving according to the organization needs.